Effect of Nebulization with Semi Fowler Position on Breath Frequency in Bronchial Asthma Patients in Grandmed Lubuk Pakam Hospital - Purba, Anita Sri Gandaria; Siregar, Salbiah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Bronchial asthma is a condition of chronic inflammation of the respiratory tract which triggers bronchial hyperactivity resulting in a feeling of heaviness in the chest and shortness of breath. Asthma patients panic easily by breathing as hard as possible when shallow and short inspirations occur. If asthma occurs for a long duration, apnea will occur and in the worst case it can result in death for the sufferer. Procedures via nebulization using the semi-Fowler position in patients with bronchial asthma can affect respiratory frequency. Nebulizer administration is a type of medication directly on targets such as the lungs so that this action can be carried out more quickly and effectively. The method in this research uses a quasi-experimental pre-test and post-test type by selecting bronchial asthma patients as respondents/sample of 15 participants who were determined using the total sampling method. Research data was collected using an observation sheet instrument containing data regarding respiratory frequency. After the intervention was given, the respondents showed that there was a decrease in respiratory frequency until it was at the normal threshold. Data analysis using a paired T-Test shows that the p-value is 0.000, which means that nebulization in the semi-Fowler position can affect the respiratory frequency of bronchial asthma patients at Grandmed Lubuk Pakam Hospital. It seems that administering nebulization in a semi-Fowler's position could be an appropriate choice in treating bronchial asthma patients in order to achieve better respiratory health.